Trusted cloud platform management model based onTPMalliance - Jun-feng TIAN; Fang-shu CHANG (Tongxin xuebao)
On the basis of trusted computing technology, trusted cloud platform architecture and management model based on theTPMalliance was proposed to solve the performance bottleneck of dynamic management of trusted nodes in the building process of trusted cloud platform. MacroTPMproposed to solve the capability limitation of TPM,the concept of time-based tree was introduced to organizeTPMalliance, addressing the problem of high time cost of nodes management in trusted cloud. It usedTPMand authentication encryption technology to solve trusted transmission problem of data among nodes inTPMalliance, and a management strategy of time-based treeTPMalliance was proposed, including node configuration protocol, node registration protocol, node logout protocol, node state real-time monitor protocol, trusted nodes management network repair protocol, node update protoc explains the production algorithm of time-based tree, analyses the effectiveness of the time cost of building trusted node management network and monitoring of node state. The simulation result indicates that the model is efficient, and the time cost in trusted node management can be reduced.